Online Current Loop Tuning for Permanent Magnet Synchronous Servo Motor Drives with Deadbeat Current Control - Zih-Cing You; Cheng-Hong Huang; Sheng-Ming Yang (Energies, 2019)
High bandwidths and accurate current controls are essential in high-performance permanent magnet synchronous (PMSM) servo drives. Compared with conventional proportional−integral control, deadbeat current control can considerably enhance the current control loop bandwidth. However, because the deadbeat current control performance is strongly affected by the variations in the electrical parameters, tuning the controller gains to achieve a satisfactory current response is crucial. Because of the prompt current response provided by the deadbeat controller, the gains must be tuned within a few control periods. Therefore, a fast online current loop tuning scheme is proposed in this paper. This scheme can accurately identify the controller gain in one current control period because the scheme is directly derived from the discrete-time motor model. Subsequently, the current loop is tuned by updating the deadbeat controller with the identified gains within eight current control periods or a speed control period. The experimental results prove that in the proposed scheme, the motor current can simultaneously have a critical-damped response equal to its reference in two current control periods. Furthermore, satisfactory current response is persistently guaranteed because of an accurate and short time delay required for the current loop tuning.